Coexistence of acid sphingomyelinase deficiency type A/B and Arnold-Chiari malformation: a novel case report - Kamalova, Aelita; Rakhmaeva, Razilya; Sageeva, Gulnara; Safiullina, Rezeda; Raimova, Adelina; Gaichik, Elena; Nasr, Dalal; Gobarah, Ayman A.; Arafat, Ahmed (Frontiers in Pediatrics, 2025)
BackgroundAcid sphingomyelinase deficiency (ASMD) type A/B, a rare lysosomal storage disorder caused by biallelic mutations in the SMPD1 gene, presents with variable visceral and neurological manifestations. Arnold-Chiari malformation is a structural defect of the cerebellum and brainstem with distinct pathogenesis and clinical course. To our knowledge, the coexistence of these two conditions has not been previously reported.Case presentationWe report the case of a 13-year-old patient diagnosed with ASMD type A/B in combination with Arnold-Chiari type I malformation, and secondary interstitial lung disease. The case presented a diagnostic challenge due to overlapping neurological features common to both conditions. The patient exhibited isolated cerebellar signs without MRI evidence of central nervous system involvement typically associated with ASMD. These findings, along with the radiological identification of cerebellar tonsillar herniation, supported Arnold-Chiari I malformation as the primary contributor to the patient's neurological deficits.ConclusionThis is the first documented case of concurrent ASMD type A/B and Arnold-Chiari malformation. The clinical overlap in neurological manifestations complicates differential diagnosis and highlights the need for careful neuroimaging assessment in patients with ASMD presenting with atypical or progressive neurological symptoms. This unique co-occurrence may suggest a broader phenotypic spectrum or a coincidental association requiring further investigation.